Concentration of Laterites Using Biomass - Wachira, Jackson M.; Muriithi, Naftali; Waithaka, Peter; Wanjau, Ruth (Kenya Industrial Property Institute, 2015)
A method of concentrating iron in laterites to make the iron extraction process economical is disclosed. Concentration using biomass yields higher levels of iron by using appropriate ratio of biomass: laterites. The concentration of iron in the laterites was done by heating a laterite/charcoal mixture in the temperature range 500-700oC in a ceramic container, a slow current of air (0.5- 0.7cm3/sec) was passed thus generating carbon monoxide in-situ. The process involves cooling and picking iron containing mineral. The optimum ratio of biomass: laterite was found to be 1:20 by mass. The iron in the raw laterites is predominantly minerals goethite, FeO.OH and haematite, Fe203, as shown by presence of peaks at diffraction angles of 20 = 21.51 ° and 20 = 54.11 °respectively. After magnetseparation iron was present predominantly as the mineral, magnetite Fe304, with diffraction peak at 20 = 36°. The percentage of iron in the magnet-separated product is increased to 55-62%.
INNOVATION BY: Naftali Muriithi; Peter Waithaka; Ruth Wanjau and Jackson Wachira Muthengia Registration no.: 93 (45)
Keywords: innovation; Laterites; Biomass